Stem Cell Therapy for Chronic Fatigue Syndrome: A Promising Approach - Deby Susanti Pada Vinski Pada Vinski; Svetlana Trofimova; Jaime Rodriguez Quintosa; Andi Kurniawan Nugroho; CA Schroeter; Stevan Jovanovic (Journal of World Science, 2024)
Chronic Fatigue Syndrome (CFS), or Myalgic Encephalomyelitis (ME), is a debilitating condition marked by persistent fatigue, cognitive dysfunction, and chronic pain, severely affecting quality of life. This study explores the potential of mesenchymal stem cell (MSC) therapy as an innovative treatment for CFS. Using a qualitative descriptive design and case studies, data were gathered through interviews, medical record reviews, and observations of patients undergoing MSC therapy. The findings revealed significant improvements in fatigue, cognitive function, and physical well-being, with participants reporting better memory, concentration, reduced pain, and improved daily functioning. While some sleep disturbances persisted, their severity was reduced. These results highlight the potential of MSC therapy to alleviate CFS symptoms and enhance quality of life. Despite its promise, challenges such as high costs, regulatory hurdles, and the need for standardized protocols persist. Further research is required to confirm long-term efficacy and safety, contributing to the growing evidence for regenerative medicine in treating chronic conditions like CFS.